2002
DOI: 10.1097/00007632-200201150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Spondylolytic Pediatric Spine Movements With Reference to Instantaneous Axis of Rotation

Abstract: The instantaneous axis of rotation deviated cranially as the stage of pars defects advanced, and as the wedge deformity increased. Kinematic alteration of the lumbar spine in pediatric patients with spondylolysis may affect chondrocytes of the endplate, perhaps contributing to the consequent spine deformities occurring secondarily to spondylolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…The IAR path was at the posterior disc-endplate space of the lower vertebra in the intact spine, and moved cranially towards the upper-posterior disc space in the lytic spine. This was in agreement with in vivo radiological data by Sakamaki et al [19]. During various loading modes, stresses in the spondylolytic pediatric model were higher than that of the intact model; ranging from 1.1 to 6.0 times, with the highest value in extension at the growth plate.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…The IAR path was at the posterior disc-endplate space of the lower vertebra in the intact spine, and moved cranially towards the upper-posterior disc space in the lytic spine. This was in agreement with in vivo radiological data by Sakamaki et al [19]. During various loading modes, stresses in the spondylolytic pediatric model were higher than that of the intact model; ranging from 1.1 to 6.0 times, with the highest value in extension at the growth plate.…”
Section: Introductionsupporting
confidence: 92%
“…His theory was further supported by MRI findings of pediatric patients with isthmic spondylolisthesis [8]. Similar conclusions were reached by Sairyo and coworkers [9,15,16,17,19,20]. They concluded from these series of investigations that the isthmic olisthesis in children and adolescents occurred based on epiphyseal separation: and proposed that pediatric isthmic spondylolisthesis is a physis stress fracture of the vertebral body.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…5,37,38,41 These changes seem to be the result of spondylolysis and spondylolisthesis rather its cause. 5,37,42,43 Recent studies elucidate that epiphyseal injury in the juvenile spine is a determining factor for progression and a cause for abnormal morphology. [42][43][44][45] Sairyo et al 46 proposed, using a rat model of lumbar spine slippage, that vertebral forward slippage in the immature spine due to separation of the epiphysis and is unrelated to disc degeneration.…”
Section: This Corresponds To a Unilateral L4 Spondylolysis (An Unusuamentioning
confidence: 99%
“…5,37,42,43 Recent studies elucidate that epiphyseal injury in the juvenile spine is a determining factor for progression and a cause for abnormal morphology. [42][43][44][45] Sairyo et al 46 proposed, using a rat model of lumbar spine slippage, that vertebral forward slippage in the immature spine due to separation of the epiphysis and is unrelated to disc degeneration. Inoue and colleagues 47 have concluded that slips with deformities of the sacral table most likely had developed in adolescence, while slips without deformity likely developed during adulthood.…”
Section: This Corresponds To a Unilateral L4 Spondylolysis (An Unusuamentioning
confidence: 99%